2000
DOI: 10.1203/00006450-200001000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Controlled Trial Comparing the Effects of Ibuprofen with Indomethacin on Cerebral Hemodynamics in Preterm Infants with Patent Ductus Arteriosus

Abstract: A prospective randomized controlled trial was performed to compare the effects of ibuprofen with indomethacin on cerebral hemodynamics measured using near infrared spectroscopy in preterm infants during treatment for patent ductus arteriosus. Infants were randomly assigned to three intravenous doses of either indomethacin (0.20-0.25 mg/kg, 12 hourly) or ibuprofen (5-10 mg/kg, 24 hourly) and also received a dose of saline. The primary end points of the study were the effects of the first dose on cerebral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
118
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(132 citation statements)
references
References 45 publications
7
118
0
7
Order By: Relevance
“…Search results and citation lists for prior publications identified 75 randomized-controlled trials of interventions that close a PDA in preterm infants. In 26 trials (five comparing long and short courses of indomethacin, [37][38][39][40][41] 19 comparing indomethacin and ibuprofen, [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and two that included very early crossover to treatment of nonresponders 29,61 ), rates of ductal closure did not differ between treatment assignments, precluding evaluation of effects of ductal closure on other outcomes, so these were excluded. The remaining 49 trials, 36, including 4728 subjects, were deemed potentially informative, as all but one documented substantial reduction in ductal patency after treatment.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
“…Search results and citation lists for prior publications identified 75 randomized-controlled trials of interventions that close a PDA in preterm infants. In 26 trials (five comparing long and short courses of indomethacin, [37][38][39][40][41] 19 comparing indomethacin and ibuprofen, [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and two that included very early crossover to treatment of nonresponders 29,61 ), rates of ductal closure did not differ between treatment assignments, precluding evaluation of effects of ductal closure on other outcomes, so these were excluded. The remaining 49 trials, 36, including 4728 subjects, were deemed potentially informative, as all but one documented substantial reduction in ductal patency after treatment.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
“…Ibuprofen is also a cyclooxygenase inhibitor, which seems to be equally effective in mediating ductal closure, while minimizing adverse renal effects (11). It has also been reported to have fewer vasoconstrictive side effects (7,8,11) compared with bolus indomethacin. However, both the absence of longterm safety data and uncertainties regarding short-term safety of ibuprofen, including possible interference with bilirubin albumin binding and an increased risk of necrotizing enterocolitis (NEC) and pulmonary hypertension (with ibuprofen tris-hydroxyamino-methane [12]) remain of concern.…”
mentioning
confidence: 99%
“…Because it purportedly lacks these side effects, ibuprofen has been proposed as a pharmacologically similar, but therapeutically preferential alternative in the treatment of PDA (5)(6)(7)(8)(9)(10)(11). Ibuprofen is also a cyclooxygenase inhibitor, which seems to be equally effective in mediating ductal closure, while minimizing adverse renal effects (11).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Published trials have also demonstrated its better safety and tolerability as compared to indomethacin and its possible role in neonatal therapeutics. [11][12][13] Since the first report of drug-bilirubin interactions in the pathogenesis of kernicterus, the potential for significant drug-bilirubin interactions has become an important consideration in neonatal drug therapy.…”
Section: Introductionmentioning
confidence: 99%